Overcoming Solar PV Intermittency using Demand Response Management in Buildings. (December 2017) - Sivaneasan, B.; Lim, M.L.; Goh, K.P.
Abstract: Singapore's National Climate Change Policy is aimed to make energy usage in Singapore more efficient, reduce pollution and expand the nation's green spaces. Part of the plan is to promote the integration of solar photovoltaics (PVs) on rooftops of high-rise HDB residential and commercial buildings. This initiative contributed to the significant growth in the integration of solar PV systems in the last few years. However, large-scale integration of solar PVs will put at risk the reliability and stability of Singapore's power system due to its intermittent nature. The intermittency problem of solar PV, typically in the range of minutes, will become very significant in Singapore as the installations of PV systems continue to increase. Conventionally, large energy storage systems are deployed as an energy buffer to compensate for the deficit or surplus of power supplied by solar PV systems. However, the high capital and maintenance costs as well as large space requirement for energy storage systems makes this an unfavorable option for building owners. This paper proposes a solution that utilizes the centrifugal fans in building air conditioning and mechanical ventilation (ACMV) system to dynamically compensate for the deficit or surplus of power supplied by solar PVs. For example, the developed solution will reduce the load demand of fans in the ACMV system equal to the drop of solar generation by controlling the speed of the fan. This will ensure that the amount of power supplied by the grid to the building will remain the same (as before the drop of solar generation) and thus no impact on the grid stability. However, since ACMV system is directly linked to building occupant comfort/health, the proposed solution will also include battery management and priority-based load shedding programs to provide support when room temperature (air conditioning) or CO level (ventilation) is above regulatory limit.